Penggunaan Model Pembelajaran Kumon dalam Meningkatkan Hasil Belajar IPA Peserta Didik Kelas VII.1 SMP Negeri 32 Tanjab Timur Semester Ganjil Tahun Ajaran 2022/2023 - Eko Rahdianto (Departement of Mathematics Education, 2022)
This study aims to obtain data and information about the use of the Kumon Learning Model in Improving Science Learning Outcomes for Class VII.1 Students of SMP Negeri 32 Tanjab Timur Odd Semester 2022/2023 Academic Year. This research is included in the type of classroom action research (CAR). This research was conducted at SMP Negeri 32 Tanjab Timur, East Tanjung Jabung Regency. This classroom action research was conducted in semester I of the 2022/2023 school year. The subjects referred to as action in this study were class VII students. 1 SMP Negeri 32 Tanjab Timur with a total of 29 students consisting of 17 boys and 12 girls. The research procedure consisted of two cycles with four research stages, starting from planning, implementing, observing and reflecting. The research data were collected using field notes, observations, interviews, and test results. In this study the data were analyzed in a quantitative descriptive manner using a percentage format. In accordance with the formulation of the problem and the research objectives that have been put forward regarding the use of the Kumon learning model in science subjects has a positive impact. So it can be concluded that the Kumon learning model can improve students' science learning outcomes in class VII SMP Negeri 32 Tanjab Timur